Penerapan Problem Based Learning Bermuatan Budaya Melayu Riau untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Sartika, Melly; Morinda, Claudio Gita; Sakur, Sakur; Armis, Armis (Papanda, 2025)
The low Mathematical Problem Solving Ability of eighth grade students of MTs Baitul Amal Pekanbaru is the background of this research. This research aims to improve the learning process to increase the mathematical problem-solving ability students o through the application of the Problem Based Learning model with the context of Riau Malay culture. This research is a Classroom Action Research. Observation techniques, discussion techniques, and test techniques are data collection techniques used in this research. The increase in students' mathematical problem-solving ability is seen from the results of the analysis of the percentage of students who obtained the maximum score and the qualifications of students' mathematical problem-solving ability. The results of the study indicate that the application of Problem Based Learning with the context of Riau Malay culture can improve the learning process and increase the mathematical problem-solving ability of eighth grade students of MTs Baitul Amal Pekanbaru on the content of two-variable linear equation systems.